DANGER AND SECURITY IN CENTRAL ASIA - MEGORAN, Nick (CENTRAL ASIA AND THE CAUCASUS, 2011)
It is the received wisdom of Western policy, journalistic and entertainment communities as well as much of the academic world of area studies that Central Asia is a source and site of particular dangers. We contend that it is time that the preconceptions and oversights of this “discourse of danger” were exposed. The question that we address in this paper is “How, why, and to what effect is Central Asia thought of and portrayed as being a particularly dangerous place?” Our answer identifies and explores a “discourse of danger” which makes the region knowable to Western officials, academic communities, journalists, and publics. By “dis course” we mean pervasive and taken-for-granted assumptions that provide a background and vocabulary for making sense of the world. We argue that the contents of much international policy and practice, news and current affairs writing, documentaries and films, and even academic studies of security, conflict and international affairs in Central Asia are derived in accordance with a preconceived “discourse of danger” which identifies threats to the West whilst ignoring insecurity as it is experienced by Central Asian communities. This article identifies and critiques this discourse of danger.The task of such geopolitical analysis is important for two reasons.Firstly, the way that policy makers think about certain places affects the way they act towards them. The Western discourse of danger thus endangers Central Asia.Secondly, this assumption of danger has profound implications for the kinds of academic research which get funded and published. Western Central Asian studies are partially shaped by assumptions of danger. This article is a challenge to this Western geopolitical vision of Central Asia.It begins by outlining the theory of critical geopolitics that we use, then overviews the portrayal of danger in Western Central Asian studies. It then considers three aspects of the discourse of danger: Central Asia as obscure, oriental, and fractious. We conclude with a call for academics to contest the discourse of danger by being attentive to alternative local narratives of danger and the wider global economic processes which are transforming society and economy in Central Asia.